Comparison of the expanded disability status scale and the functional independence measure in patients with multiple sclerosis: Primerjava uporabe razširjene lestvice stopnje zmanjšane zmožnosti (EDSS) in lestvice funkcionalne neodvisnosti (FIM) pri bolnikih z multiplo sklerozo - Čelan , Nastasja; Čelan , Dušan; Jesenšek Papež , Breda (Acta Medico-Biotechnica, 2023)
Objective: This study aimed to evaluate scales that are used to follow up on the condition and course of rehabilitation for an objective assessment of patients with multiple sclerosis. The most commonly used scale is the Expanded Disability Status Scale (EDSS) for obtaining information on neurological impairments. The main disadvantage of this scale is that it focuses a lot on the ability to walk and is not adequately sensitive for detecting the changes in the patient in time. The Functional Independence Measure (FIM) is the most commonly used scale in rehabilitation. It evaluates the ability of patients to perform daily activities, for example, feeding and dressing. In the study, we focused on the comparison of EDSS and FIM to ascertain the applicability of FIM in patients with multiple sclerosis. Methods: We performed a cross-sectional study of 38 patients with multiple sclerosis by talking to the patients and reviewing the medical documentation where the EDSS evaluation was conducted. Then, we evaluated the patient using the FIM scale. The data were processed using the IBM SPSS Statistics 25 software and displayed graphically using the Microsoft Excel program. Results: The statistical analysis showed a strong negative correlation between EDSS and FIM (r = -0.731). The motor part of the FIM scale had a strong negative correlation with EDSS (r = -0.732). The cognitive part had a weak negative correlation (r = -0.262). The sex and the duration of the disease did not impact the FIM evaluation significantly. The age had a moderately strong negative correlation (r = -0.396). Conclusion: We proposed that FIM was a useful scale for the routine evaluation of patients in the clinical environment.